2014
DOI: 10.1002/ajmg.a.36651
|View full text |Cite
|
Sign up to set email alerts
|

Activating PIK3CA somatic mutation in congenital unilateral isolated muscle overgrowth of the upper extremity

Abstract: Congenital unilateral overgrowth of the upper extremity affecting only the muscle tissue is rare. We describe on the clinical, histopathological, and neuroimaging findings in a 6-year-old girl with a congenital, non-progressive muscle enlargement of the entire left upper limb with an ipsilateral hand deformity. No cutaneous stigmata or additional features were detected. Sanger sequencing for the AKT1, PIK3CA, and PTEN genes identified an activating c.3140A>G, p.H1047R mutation in the PIK3CA gene from the affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In order to characterize the mutation spectrum of patients with congenital/early childhood onset PROS without overgrowth of the brain, we performed an extensive literature search, and have presented the results together with the data of the seven patients described here [Kurek et al, ; Lindhurst et al, ; Rios et al, ; Castiglioni et al, ; Cohen et al, ; Emrick et al, ; Keppler‐Noreuil et al, ; Maclellan et al, ; Rasmussen et al, ; Couto et al, ; Limaye et al, ; Loconte et al, ; Luks et al, ; Osborn et al, ; Castillo et al, ; Hucthagowder et al, ; Mirzaa et al, ; Tripolszki et al, ]. We found that the three highly recurrent cancer‐associated mutations, p.(Glu542Lys), p.(Glu545Lys), and p.(His1047Arg) [Mirzaa et al, ], can be seen in about 70% of patients with PROS; whereas p.(Cys420Arg) and p.(His1047Leu) accounts for nearly 20% of the patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In order to characterize the mutation spectrum of patients with congenital/early childhood onset PROS without overgrowth of the brain, we performed an extensive literature search, and have presented the results together with the data of the seven patients described here [Kurek et al, ; Lindhurst et al, ; Rios et al, ; Castiglioni et al, ; Cohen et al, ; Emrick et al, ; Keppler‐Noreuil et al, ; Maclellan et al, ; Rasmussen et al, ; Couto et al, ; Limaye et al, ; Loconte et al, ; Luks et al, ; Osborn et al, ; Castillo et al, ; Hucthagowder et al, ; Mirzaa et al, ; Tripolszki et al, ]. We found that the three highly recurrent cancer‐associated mutations, p.(Glu542Lys), p.(Glu545Lys), and p.(His1047Arg) [Mirzaa et al, ], can be seen in about 70% of patients with PROS; whereas p.(Cys420Arg) and p.(His1047Leu) accounts for nearly 20% of the patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 The variable expression of symptoms within PROS is mainly explained by the timing and location of the initiating PIK3CA mutation, but the reason behind the high degree of interindividual phenotypic heterogeneity is unknown. 7,8 Somatic activating PIK3CA mutations are common in at least 12 different cancer types. 5 It has been proposed that an increased number of neuromuscular junctions and a change in the muscle-tendon ratio is involved in muscle hypertrophy development.…”
Section: Introductionmentioning
confidence: 99%
“…6 The etiology remains still undetermined but it has recently been reported that isolated congenital muscular upper limb overgrowth can be related to somatic mosaic PIK3CA mutations. 7,8 Somatic activating PIK3CA mutations are common in at least 12 different cancer types. 1,[9][10][11] Previous studies show that the same PIK3CA hotspot mutations found in cancer are found in PROS.…”
Section: Introductionmentioning
confidence: 99%
“…We also found two similar cases reported in the Genetics literature. Castiglioni et al [10] reported on a 6-year old girl with unilateral isolated upper limb muscle overgrowth. The authors only commented on the ulnar drift of the index finger; although the illustrations also showed hypoplasia of the index finger.…”
Section: Discussionmentioning
confidence: 99%